(untitled) - Hase, Yoshihide (Chichester ; Hoboken, NJ, 2007)
Maintaining the reliable and efficient generation, transmission and distribution of electrical power is of the utmost importance in a world where electricity is the inevitable means of energy acquisition, transportation, and utilization, and the principle mode of communicating media. Our modern society is entirely dependent on electricity, so problems involving the continuous delivery of power can lead to the disruption and breakdown of vital economic and social infrastructures.
Keywords: Electric power systems,Hệ thống điện năng